Reconstructing Contemporary Legal Methodology through the Noetic Triadic Spiral Model: A Trans-Epistemological Perspective - Kelik Wardiono; Arief Budiono; Isman Isman; Arova Bakhtiar; Dwinuryidha Ken Rifqi (MILRev: Metro Islamic Law Review, 2026)
This study aims to reconstruct contemporary legal methodology by proposing the Noetic Triadic Spiral Model as a trans-epistemological framework that integrates revelation (waḥy), reason (ʿaql), and empirical reality (wāqiʿ) in a dynamic and iterative structure. The research responds to the growing epistemic fragmentation between normative-textual approaches and socio-empirical legal reasoning in contemporary Islamic legal thought. It seeks to formulate a methodological model that bridges classical uṣūl al-fiqh with contemporary interdisciplinary demands without undermining its theological foundations. This research employs a qualitative normative-philosophical approach combined with conceptual analysis and critical hermeneutics. Primary sources include classical works of uṣūl al-fiqh and modern reformist legal theories, which are analyzed through a comparative-constructive method. The study also incorporates epistemological mapping to identify structural tensions between scriptural authority, rational deliberation, and socio-historical contingencies. Through this approach, the Noetic Triadic Spiral Model is formulated as a spiral (rather than linear) interaction among three epistemic domains, emphasizing continuous reinterpretation, reflexivity, and contextual validation. The findings demonstrate that the proposed model offers a coherent methodological reconstruction that transcends the dichotomy between textualism and contextualism. By conceptualizing legal reasoning as a spiral process of noetic engagement—where revelation provides normative orientation, reason ensures coherence and systematicity, and empirical reality functions as a field of verification—the model strengthens methodological adaptability while preserving doctrinal integrity. The spiral nature ensures that interpretation remains open to revision without collapsing into relativism. The scientific contribution of this study lies in its formulation of a trans-epistemological paradigm that rearticulates legal methodology beyond classical dualisms. It provides a theoretical bridge between traditional jurisprudential structures and contemporary legal challenges, contributing to ongoing debates on reform, renewal (tajdīd), and methodological integration in legal theory. The Noetic Triadic Spiral Model thus offers an innovative framework for rethinking legal reasoning in a plural, complex, and rapidly evolving global context.